Exposure to Odors Increases Pain Threshold in Chronic Low Back Pain Patients. Issue 10 (14th April 2020) - Gossrau, Gudrun; Baum, Daniel; Koch, Thea; Sabatowski, Rainer; Hummel, Thomas; Haehner, Antje
Abstract: Objectives: Structured exposure to odors is an acknowledged therapy in patients with smell loss but has also been shown to be effective in depression. The latter might rely on connections between olfactory and emotional structures, suggesting possible effects of a similar approach in pain patients. Based on neuroanatomy, there are several interfaces between the "pain matrix" and olfactory system, such as the limbic system, hypothalamus, and mediodorsal thalamus. We aimed to investigate whether structured exposure to odors may impact perceived pain in patients with chronic low back pain. Design: Randomized controlled parallel-group design. Subjects were tested on two occasions, at baseline and after four weeks. Setting: Ambulatory. Subjects: Forty-two patients with chronic low back pain Methods: For all patients, olfactory function (using the "Sniffin'Sticks" test kit), detection, and pain thresholds for cutaneous electrical stimuli (applied to the forearm) were tested at baseline and after four weeks. Twenty-eight patients exposed themselves to four odors (rose, vanilla, chocolate, peach) every two hours over a period of four weeks (training group). Control patients (N = 14) underwent no such "olfactory training" (nontraining group). Results: Pain thresholds were significantly increased in patients who performed olfactory training compared with patients who did not train with odors. Detection thresholds and olfactory function remained unchanged. Conclusions: The present results indicate that regular exposure to odors increases pain thresholds in patients with chronic back pain and could be useful for general pain control in these patients. Furthermore, olfactory training in chronic pain patients might help to reduce chronification of pain by desensitization.